International study of definitions of English-language terms for suicidal behaviours: a survey exploring preferred terminology. Issue 2 (9th February 2021) - De Leo, Diego; Goodfellow, Benjamin; Silverman, Morton; Berman, Alan; Mann, John; Arensman, Ella; Hawton, Keith; Phillips, M R; Vijayakumar, Lakshmi; Andriessen, Karl; Chavez-Hernandez, Ana-Maria; Heisel, Marnin; et al.
Abstract : Objectives: Explore international consensus on nomenclatures of suicidal behaviours and analyse differences in terminology between high-income countries (HICs) and low/middle-income countries (LMICs). Design: An online survey of members of the International Organisation for Suicide Prevention (IASP) used multiple-choice questions and vignettes to assess the four dimensions of the definition of suicidal behaviour: outcome, intent, knowledge and agency. Setting: International. Participants: Respondents included 126 individuals, 37 from 30 LMICs and 89 from 33 HICs. They included 40 IASP national representatives (65% response rate), IASP regular members (20% response rate) and six respondents from six additional countries identified by other organisations. Outcome measures: Definitions of English-language terms for suicidal behaviours. Results: The recommended definition of 'suicide' describes a fatal act initiated and carried out by the actors themselves. The definition of 'suicide attempt' was restricted to non-fatal acts with intent to die, whereas definition of 'self-harm' more broadly referred to acts with varying motives, including the wish to die. Almost all respondents agreed about the definitions of 'suicidal ideation', 'death wishes' and 'suicide plan'. 'Aborted suicide attempt' and 'interrupted suicide attempt' were not considered components of 'preparatory suicidal behaviour'. There were several differences between representatives from HICs and LMICs. Conclusion: This international opinion survey provided the basis for developing a transcultural nomenclature of suicidal behaviour. Future developments of this nomenclature should be tested in larger samples of professionals, including LMICs may be a challenge.